Relationship between characteristics and self-care toward blood pressure in hypertensive patients - Mu’afiro, Adin; Nursalam; Sriyono; Suwito, Joko; Hidayati, Sri (Gaceta Médica de Caracas, 2026)
Introduction: Successful hypertension management depends on patients’ self-care abilities, including medication adherence, healthy lifestyle behaviors, and blood pressure monitoring, which may vary with age, gender, education, and duration of hypertension. The purpose of the study is to examine the relationships among characteristics, self-care maintenance, blood pressure monitoring, and management in hypertensive patients.